The role of the advertising agency: Standardization/adaptation - Aygul Isayeva (IBSU Scientific Journal (IBSUSJ), 2011)
In this article the role of advertising agency in global marketing strategy has been examined. The developed matrix examines the contingencies that influence the success of the company's global advertising strategy. This research reviews how the company, as the principal, may determine the nature of its relationship with the advertising agency and the degree of adaptation vs. standardization necessary in each situation.
Keywords: M37; 330; advertising agency; adaptation; standardization